الأرشيف الوطني لدولة الإمارات العربية المتحدة : دراسة تحليلية استشرافية - نقبي، هزاع هاشم محمد عبد الله (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2021)
This study aims to analyze and evaluate the emergence and development of the National Archives of the United Arab Emirates, the change of the old concept of the archive among the employees of government agencies, and the inculcation of the importance of historical documents that contribute to accessing information that the decision-makers can rely on, and to limit its loss and destruction. To build an integrated and modern archive system that determines the chronological age of documents, and to preserve these documents, it is necessary to strive to rehabilitate warehouses for preserving the intermediate archive in the building of each government agency within the approved international specifications and standards. In this study, we have reviewed the stages of the National Archives of the United Arab Emirates, starting from its inception until it became a center that has a prominent role at the local, regional and global levels. We have also described the emergence of the National Archives of the United Arab Emirates and the stages and challenges that it faces by collecting historical records and linking them to the results of the field survey between university students and government employees. We have used a comparative method to compare the National Archives of the United Arab Emirates to the regional and global counterparts. The study reached a set of results, including building a strategy that defines the scope of archiving applications and various archiving chains as the cornerstone and base on which all the activities and tasks of the successive archiving system design will be based. The archive is considered a source of information as it is a civilizational and cultural heritage that bears witness to the history and identity of nations and preserves their civilizational symbols and national sovereignty. For this reason, the countries of the world have given the archives special attention and care.